The Influence of Attitudes, Subjective Norms and Perception Behavior Control on Taxpayer Compliance of Swallow's Nest in Kendari City - Burhanuddin, Burhanuddin; Umar Sakka, Gjosphink Putra; Hasnita, Nita (Dinasti Publisher, 2025)
The purpose of this study is to analyze: 1) the influence of attitudes on the compliance of swallow's nest taxpayers; 2) the influence of subjective norms on the compliance of swallow's nest taxpayers; and 3) the effect of perception behavior control on the compliance of swallow's nest taxpayers. The data used is primary data obtained through questionnaires. Data analysis was carried out by multiple linear regression. The results of the study show that: 1) Attitude does not have a significant influence on the compliance of swallow's nest taxpayers in Kendari City; 2) Subjective norms have a significant positive effect on the compliance of swallow's nest taxpayers in Kendari City; and 3) Perception behavior control has a significant positive effect on the compliance of swallow's nest taxpayers in Kendari City.